Autism and esophageal achalasia in childhood: a possible correlation? Report on three cases. Issue 3 (18th May 2012) - Betalli, P.; Carretto, E.; Cananzi, M.; Zanatta, L.; Salvador, R.; Galeazzi, F.; Guariso, G.; Gamba, P.; Costantini, M.
SUMMARY Chronic gastrointestinal symptoms are commonly reported in autistic patients. Dysphagia is often present, and it is generally related to behavioral eating disorders. The association between autism and esophageal achalasia has not been described in literature yet. We report our experience with three cases of autistic children we recently treated for esophageal achalasia. In the first case (a 14‐year‐old male), achalasia was diagnosed with barium swallow and esophageal manometry and was successfully treated with three pneumatic endoscopic dilatations (follow‐up: 3 years). In the second case (a 12‐year‐old female), achalasia was diagnosed with barium swallow and esophageal manometry and was treated with Heller myotomy after two unsuccessful pneumatic endoscopic attempts (follow‐up: 3 months). In the last case, a 15‐year‐old male underwent barium swallow and endoscopy that confirmed achalasia. He was treated with Heller myotomy, and he is asymptomatic at a 6‐month follow‐up. To our knowledge, this is the first report of a possible association between autism and esophageal achalasia. Because of the rarity of both diseases, their association in the same patient is unlikely to be casual even if speculation on their common etiology is impossible at present. This finding needs further confirmation, but it is sufficient, in our opinion, to indicate proper evaluation with barium swallow and/or manometry in any autistic children with eating difficulty.